O setor elétrico entre a questão histórica e os problemas sociológicos - Alessandro André Leme (Ciências Sociais Unisinos)
The end of the 20 th century was characterized by a complex process and great transfor- mations in the global sphere, where globalization, neo-liberalism and market-oriented reforms acquire theoretical relevance among researchers, scientists and intellectuals of various fields of knowledge and practical relevance in the macro-economic and political-institutional direction adopted, either integrally or in part, by several countries in the world, especially by developing countries, including Brazil. Out of this process we highlight the changes in the electric sector, which is understood as a strategic one. The reflection on the electric sector involves understanding it in its complexity, i.e., from the economic, institutional and political point of view, taking into account its various actors (both private and public agents) and at the same time the responses given by the State to these movements, actors and pressures.